Factors interfering in the accession or not of individual Protection equipment by rural workers (Research, Society and Development, 2020)
To identify the factors that interfere in the non adherence of the use of personal protective equipment by rural workers. This is an integrative literature review, carried out in the following databases Latin American and Caribbean Literature in Health Sciences, US National Library of Medicine and SciVerse Scopus. The corpus of the study consisted of 15 publications. It was evidenced that factors that influence the adhesion or non-adherence of individual protection equipment are: individual factors such as low perception of risk and working time and the factors related to work as lack of orientation and discomfort. It can be concluded that there are several factors that influence the adherence or not of rural workers to the use of personal protective equipment. It is important to highlight the need to raise awareness among these workers about the importance of using this equipment.